2001
DOI: 10.1002/jcop.1048
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structure of the Perceived Neighborhood Scale (PNS): A test of longitudinal invariance

Abstract: ⅢThis article analyzes the invariance of the factor structure of the Perceived Neighborhood Scale (PNS)-a measure of neighborhood perceptions for parents of young children-across two waves of data. Scale items were theoretically derived to represent four dimensions of neighborhood context: social embeddedness, sense of community, satisfaction with neighborhood, and fear of crime. The longitudinal invariance of the factor structure of the scale was confirmed by testing the goodness-of-fit of four nested models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 52 publications
4
89
0
2
Order By: Relevance
“…This supports common findings in the neighborhood literature (e.g., Martinez et al 2002;Prezza et al 2001;Zeldin and Topitzes 2002) and underscores that certain features of neighborhoods may operate similarly for persons with serious mental illness living in their own apartments as they do among people without a mental illness diagnosis. This does not mean that it is appropriate to generalize all neighborhood research findings from non-mentally ill populations to people with SMI; but it does suggest that important features that help people feel a sense of community-including safety, neighbor relations, and satisfaction-may be common across populations.…”
Section: Experiences and Factors Associated With Sense Of Communitysupporting
confidence: 86%
See 2 more Smart Citations
“…This supports common findings in the neighborhood literature (e.g., Martinez et al 2002;Prezza et al 2001;Zeldin and Topitzes 2002) and underscores that certain features of neighborhoods may operate similarly for persons with serious mental illness living in their own apartments as they do among people without a mental illness diagnosis. This does not mean that it is appropriate to generalize all neighborhood research findings from non-mentally ill populations to people with SMI; but it does suggest that important features that help people feel a sense of community-including safety, neighbor relations, and satisfaction-may be common across populations.…”
Section: Experiences and Factors Associated With Sense Of Communitysupporting
confidence: 86%
“…In a study of 1,213 residents of a transitional urban neighborhood in Nashville, TN, Chavis and Wandersman (1990) found block satisfaction and sense of community to be positively related. Similarly, Martinez et al (2002) reported a significant relationship between satisfaction with the neighborhood and sense of community. Understanding the connection between neighborhood satisfaction and sense of community for persons with serious mental illness is of interest because data shows that when individuals with SMI are asked to rate their neighborhoods on a scale of 1 to 10, their ratings are as much as 20 percent lower than those of all other households on the block (Newman 1994).…”
Section: Neighborhood Satisfactionmentioning
confidence: 89%
See 1 more Smart Citation
“…Research findings show that higher perceptions of neighborhood safety are related to perceptions of neighborhood connection and sense of community (Zeldin and Topitzes 2002;Ziersch et al 2005), whereas perceptions of higher neighborhood crime are negatively related to sense of community (Martinez et al 2001). When residents perceive their neighborhoods to be unsafe, feelings of danger may overtake their daily lives, causing them to stay isolated in their homes and refuse to reach out to fellow residents (Zeldin and Topitzes 2002).…”
Section: Predictors Of Neighborhood Social Climatementioning
confidence: 97%
“…En tal sentido, se ha analizado la forma en que las condiciones físicas, sociales y económicas de la colonia influyen en la satisfacción con ésta, lo que a su vez determina el nivel de satisfacción con la vida (Salleh y Badarulzaman, 2012;Miller et al, 1980); también ha sido importante determinar cómo el grado de satisfacción es un factor que influye en las decisiones de mudarse de los residentes (Clark et al, 2006;Brower, 2003;Droettboom et al, 1971;Kasl y Harburg, 1972;Lee et al, 1994;Nathanson et al, 1976;Newman y Duncan, 1979;Quigley y Weinberg, 1977); en el nivel o calidad de vida (Campbell et al, 1976;Sirgy et al, 2000;McCrea et al, 2005;Sirgy y Cornwell, 2002;Parkes et al, 2002), así como en la educación que reciben los hijos en el hogar (Martinez et al, 2002). Se ha reconocido que los residentes que experimentan mayor satisfacción con su colonia reportan mejor salud mental, perciben menos inseguridad y muestran una menor probabilidad de mudarse (Baba y Austin, 1989;Adams, 1992;Bolan, 1997;Sirgy y Cornwell, 2002;Austin et al, 2002;Oh, 2003).…”
Section: Literatura En Torno a La Satisfacción Con La Coloniaunclassified